Risk Assessment of Recreational Noise–Induced Hearing Loss from Exposure through a Personal Audio System—iPod Touch - Gopal, Kamakshi V.; Mills, Liana E.; Phillips, Bryce S.; Nandy, Rajesh (Journal of the American Academy of Audiology, 2019)
Recreational noise–induced hearing loss (RNIHL) is a major health issue and presents a huge economic burden on society. Exposure to loud music is not considered hazardous in our society because music is thought to be a source of relaxation and entertainment. However, there is evidence that regardless of the sound source, frequent exposure to loud music, including through personal audio systems (PAS), can lead to hearing loss, tinnitus, difficulty processing speech, and increased susceptibility to age-related hearing loss.Several studies have documented temporary threshold shifts (TTS) (a risk indicator of future permanent impairment) in subjects that listen to loud music through their PAS. However, there is not enough information regarding volume settings that may be considered to be safe. As a primary step toward quantifying the risk of RNIHL through PAS, we assessed changes in auditory test measures before and after exposure to music through the popular iPod Touch device set at various volume levels.This project design incorporated aspects of both between- and within-subjects and used repeated measures to analyze individual groups.A total of 40 adults, aged 18–31 years with normal hearing were recruited and randomly distributed to four groups. Each group consisted of five males and five females.Subjects underwent two rounds of testing (pre- and postmusic exposure), with a 30-min interval, where they listened to a playlist consisting of popular songs through an iPod at 100%, 75%, 50%, or 0% volume (no music). Based on our analysis on the Knowles Electronic Manikin for Acoustic Research, with a standardized 711 coupler, it was determined that listening to the playlist for 30 min through standard earbuds resulted in an average level of 97.0 dBC at 100% volume, 83.3 dBC at 75% volume, and 65.6 dBC at 50% volume. Pure-tone thresholds from 500–8000 Hz, extended high-frequency pure tones between 9–12.5 kHz, and distortion product otoacoustic emissions (DPOAE) were obtained before and after the 30-min music exposure. Analysis of variance (ANOVA) was performed with two between-subjects factors (volume and gender) and one within-subjects factor (frequency). Change (shift) in auditory test measures was used as the outcome for the ANOVA.Results indicated significant worsening of pure-tone thresholds following music exposure only in the group that was exposed to 100% volume at the following frequencies: 2, 3, 4, 6 and 8 kHz. DPOAEs showed significant decrease at 2000 and 2822 Hz, also only for the 100% volume condition. No significant changes were found between pre- and postmusic exposure measures in groups exposed to 75%, 50%, or 0% volume conditions. Follow-up evaluations conducted a week later indicated that pure-tone thresholds had returned to the premusic exposure levels.These results provide quantifiable information regarding safe volume control settings on the iPod Touch with standard earbuds. Listening to music using the iPod Touch at 100% volume setting for as little as 30 min leads to TTS and worsening of otoacoustic emissions, a risk for permanent auditory damage.
Keywords: iPod; personal audio systems; pure-tone thresholds; recreational noise–induced hearing loss; temporary threshold shift